Tenofovir disoproxil fumarate initiation and changes in urinary biomarker concentrations among HIV-infected men and women. (15th March 2019) - Zhang, William R.; Scherzer, Rebecca; Estrella, Michelle M.; Ascher, Simon B.; Muiru, Anthony; Jotwani, Vasantha; Grunfeld, Carl; Parikh, Chirag R.; Gustafson, Deborah; Kassaye, Seble; Sharma, Anjali; Cohen, Mardge; et al.
Abstract : Objectives: Urinary biomarkers of kidney injury may have potential to identify subclinical injury attributable to tenofovir disoproxil fumarate (TDF) toxicity. Design: This observational study included 198 HIV-infected participants from the Multicenter AIDS Cohort Study and the Women's Interagency HIV Study, who initiated TDF between 2009 and 2015 and had urine samples collected at baseline before and after TDF initiation. Methods: We used linear mixed-effects models controlling for urine creatinine and time on TDF to evaluate the effects of TDF initiation on changes in 14 urinary biomarkers. Results: Within 1 year after TDF initiation, concentrations of trefoil factor 3 [+78%; 95% confidence interval (CI) +38%, +129%), alpha-1 microglobulin (α1m) (+32%; 95% CI +13%, +55%), clusterin (+21%; 95% CI +6%, +38%), uromodulin (+19%; 95% CI +4%, +36%), and kidney injury molecule-1 (KIM-1) (+13%; 95% CI +1%, +26%) significantly increased, whereas interleukin-18 (IL-18) significantly decreased (−13%, 95% CI −7%, −25%). Subsequent to the first year of TDF use, biomarker concentrations stabilized, and these changes were not statistically significant. When stratifying by baseline viremia (HIV-1 RNA < vs. ≥80 copies/ml), concentration changes for most biomarkers during the first year of TDF use were greater among aviremic vs. viremic participants, with significant differences in α1m (+80 vs. +22%), KIM-1 (+43 vs. +10%), beta-2 microglobulin (+83 vs. −10%), YKL-40 (+33 vs. −5%), and IL-18 (+20 vs. −27%). Conclusions: TDF initiation was associated with substantial changes in urinary biomarkers of kidney injury within the first year of use, particularly among aviremic participants. A urinary biomarker panel may be a clinically useful tool to detect and monitor the heterogeneous effects of TDF on the kidney. Abstract : Supplemental Digital Content is available in the text